Advanced Maintenance Modelling for Asset Management Techniques and Methods for Complex Industrial Systems - Crespo Márquez, Adolfo; González-Prida Díaz, Vicente; Gómez Fernández, Juan Francisco.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book promotes and describes the application of objective and effective decision making in asset management based on mathematical models and practical techniques that can be easily implemented in organizations. This comprehensive and timely publication will be an essential reference source, building on available literature in the field of asset management while laying the groundwork for further research breakthroughs in this field. The text provides the resources necessary for managers, technology developers, scientists and engineers to adopt and implement better decision making based on models and techniques that contribute to recognizing risks and uncertainties and, in general terms, to the important role of asset management to increase competitiveness in organizations.
Part I: Introduction -- Chapter 1: Asset Management in the Context of the Industry 4.0 -- Part II: A Changing Asset Management Framework -- Chapter 2: A Maintenance Management Framework Based on PAS 55 -- Chapter 3: The Integration of Open Reliability, Maintenance and Condition Monitoring Management Systems -- Chapter 4: Prognostics and Health Management in Advanced Maintenance Systems -- Chapter 5: A Framework for Effective Management of CBM Programs -- Part III: Pursuing High Management Effectiveness in a Dynamic Environment -- Chapter 6: Criticality Analysis for Maintenance Purposes -- Chapter 7: AHP Method Adapted to a Changing Environment -- Chapter 8: Reliability Stochastic Modeling for Repairable Physical Assets. Case Study Applied to the Chilean Mining -- Chapter 9: Economic Impact of a Failure Using Life Cycle Cost Analysis -- Part IV: Advanced Methods and Techniques to Improve Management Efficiency -- Chapter 10: On-line Reliability and Risk to Schedule the Preventive Maintenance in Network Utilities -- Chapter 11: Customer-oriented Risk Assessment in Network Utilities -- Chapter 12: Analysis of Dynamic Reliability Surveillance.-Part V: The Need for Innovation in Assessment and Control -- Chapter 13: A Quantitative Graphical Analysis to Support Maintenance -- Chapter 14: Case Study of Graphical Analysis for Maintenance Management -- Chapter 15: A Graphical Method to Support Operation Performance Assessment -- Chapter 16: A Practical Method for the Maintainability Assessment -- Part VI: Continuous Improvement Through Emergent Process and Technologies.-Chapter 17: Value-driven Engineering of E-Maintenance Platforms -- Chapter 18: Assistance to Dynamic Maintenance Tasks by Ann Based Models -- Chapter 19: Availability Model Under Overcapacity and Load Sharing Restrictions -- Chapter 20: Influence of the Input Load on the Reliability of the Grinding Line -- Part VII: Results and Conclusions -- Chapter 21: Summary of Result and Conclusions.
Keywords: Industrial Management; Mathematical optimization; Probabilities; Production management; Security systems; Operations research; Industrial Management; Optimization; Probability Theory; Operations Management; Security Science and Technology; Operations Research and Decision Theory